Antifungal Activity Against Phytophthora capsici leon Which Causes Root Neck Burn in Pepper Around Kahramanmaras - EREN KIRAN*, ÖZLEM; ILÇIM, AHMET; DIGRAK, METIN (Asian Journal of Chemistry, 2024)
In the present study effects of essential oil and extracts obtained from plants on Phytophthora capsici leon which is a pathogen fungus for pepper plants (Capsicum annuum L.) have been investigated. Essential oils and chloroform, methanol and hexane extracts of various plants including Pistachia terebinthus L., Quercus infectoria Oliv., Pinus brutia TEN., Juniperus oxycedrus L., Cedrus libani A.Rich., Pinus nigra L., Abies cilicica Carr., Salvia aucheri L., Phlomis bourgei Boiss., Parmelia furfuracea L., Crocus chrysanthus (Herb.) Herb., Rumex scutatus L., Myrtus communis L., Eugenia caryophyllata Thumb., Smyrnium olusatrum L., Ajuga orientalis L., Astragalus schizopterus Boiss., Papaver hybridum L. Salvia multicaulis Vahl., Salvia viridis L., Satureja cilicica P.H., Satureja hortensis L., have been used. It has been found that essential oils and extracts of some plants have repressive effect on growth of Phytophthora capsici.